2020
DOI: 10.1111/fog.12495
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in feeding of Pacific saury Cololabis saira in June and July in the North Pacific Ocean

Abstract: Gut contents of Pacific saury Cololabis saira during their feeding migration through a transition zone between subtropical and subarctic waters in the North Pacific Ocean are reported. Geographic changes in feeding habits and preferences are described for the months of June and July, for the years 2012, 2016, and 2017. Pacific saury prey comprised 27 taxa. Cluster analysis based on numerical abundance of these prey taxa in guts indicated six Pacific saury feeding types (A to F) existed. Of these, types A–E occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…In fact, some studies have reported impacts of MHWs on lower trophic levels of marine ecosystems (e.g., [38,39]). Commercially important fisheries' resources include Japanese sardine Sardinops melanostictus and Pacific saury Cololabis saira, which utilize the northwestern Pacific waters around the focal area as a nursery ground in summer (e.g., [40,41]). Hence, for sustainable management of ecosystems in the northwestern Pacific Ocean, physical and biological studies are essential, not only to evaluate influences of the 2021 MHWs but also to project the influences of future MHWs on marine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies have reported impacts of MHWs on lower trophic levels of marine ecosystems (e.g., [38,39]). Commercially important fisheries' resources include Japanese sardine Sardinops melanostictus and Pacific saury Cololabis saira, which utilize the northwestern Pacific waters around the focal area as a nursery ground in summer (e.g., [40,41]). Hence, for sustainable management of ecosystems in the northwestern Pacific Ocean, physical and biological studies are essential, not only to evaluate influences of the 2021 MHWs but also to project the influences of future MHWs on marine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Growth, feeding, distribution, and migratory patterns of Pacific saury are all affected by SST 29 31 . The geographic distributions and abundances of Pacific saury fishing stocks in the northwestern Pacific are strongly linked to sea temperatures 9 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Important food sources for Pacific saury in summer are large copepods, especially Neocalanus spp. (Miyamoto et al, 2020;Odate, 1994). The biomass of Neocalanus copepods varies interannually (Tadokoro et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hatched larvae and juveniles are transported east along the Kuroshio Extension (Oozeki et al, 2015), after which they migrate north from subtropical regions into subarctic Oyashio waters from May to July (Fukushima, 1979). There they feed on the abundant copepods which occur in those regions (Miyamoto et al, 2020; Odate, 1994). Subsequently, they commence spawning migration towards the west in August or September (Kakehi et al, 2020; Miyamoto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%